Socio-Cultural Changes in Modernization and Technology Viewed From The Learning Process - Miftakhul Rizqi; Muchlis Budiman; M. Dicky Reza (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
The development of information and communication technology in modernization has revolutionized learning and access to information. This study aims to describe the socio-cultural changes in educational institutions and how to implement the learning process in digital literacy. This study uses a qualitative approach using literature reviews such as academic articles, research papers, and books that explore the relationship between modernization, technology, and socio-cultural change, emphasizing the role of the learning process. The results show that there are socio-cultural changes in the scope of educational institutions amid technological modernization. Technological developments affect learning methods in an educational institution. Technology is also changing how teachers and students seek learning resources. Technology also creates how distance learning can be done using video conferencing platforms. The impact of technology and modernization has changed the way students interact and communicate in the school environment. Educational institutions also try to adapt the curriculum to the needs of modern society. The digital literacy-based learning process also has an impact when the vast internet technology and information technology global knowledge have become more accessible through local or national and international dimensions. The role of social media and other digital platforms in the learning process influences how people create and maintain their digital identities.